BoLA-DRB3 Polymorphism is Associated with Differential Susceptibility to Bovine Leukemia Virus-Induced Lymphoma and Proviral Load - Lo, Chieh-Wen; Borjigin, Liushiqi; Saito, Susumu; Fukunaga, Koya; Saitou, Etsuko; Okazaki, Katsunori; Mizutani, Tetsuya; Wada, Satoshi; Takeshima, Shin-nosuke; Aida, Yoko (Viruses, 2020)
Bovine leukemia virus (BLV) is the causative agent of enzootic bovine leucosis. However, less than 5% of BLV-infected cattle will develop lymphoma, suggesting that, in addition to viral infection, host genetic polymorphisms might play a role in disease susceptibility. Bovine leukocyte antigen (BoLA)-DRB3 is a highly polymorphic gene associated with BLV proviral load (PVL) susceptibility. Due to the fact that PVL is positively associated with disease progression, it is believed that controlling PVL can prevent lymphoma development. Thus, many studies have focused on the relationship between PVL and BoLA-DRB3. Despite this, there is little information regarding the relationship between lymphoma and BoLA-DRB3. Furthermore, whether or not PVL-associated BoLA-DRB3 is linked to lymphoma-associated BoLA-DRB3 has not been clarified. Here, we investigated whether or not lymphoma-associated BoLA-DRB3 is correlated with PVL-associated BoLA-DRB3. We demonstrate that two BoLA-DRB3 alleles were specifically associated with lymphoma resistance (*010:01 and *011:01), but no lymphoma-specific susceptibility alleles were found; furthermore, two other alleles, *002:01 and *012:01, were associated with PVL resistance and susceptibility, respectively. In contrast, lymphoma and PVL shared two resistance-associated (DRB3*014:01:01 and *009:02) BoLA-DRB3 alleles. Interestingly, we found that PVL associated alleles, but not lymphoma associated alleles, are related with the anti-BLV gp51 antibody production level in cows. Overall, our study is the first to demonstrate that the BoLA-DRB3 polymorphism confers differential susceptibility to BLV-induced lymphoma and PVL.